Evaluation of the convective heat transfer coefficient of human body and its effect on the human thermoregulation predictions. (June 2021) - Xu, Jingxian; Psikuta, Agnes; Li, Jun; Annaheim, Simon; Rossi, René M.
Abstract: Human thermoregulation models, particularly the Fiala model, are well accepted for the prediction of thermoregulatory responses and the assessment of clothing and building systems with regard to human thermal comfort. However, the convective heat transfer coefficients ( h c ), used for the heat transfer calculations, were obtained from measurements with a thermal manikin with poor body resolution from decades ago, and they were not distinguished between body postures. In this study, the overall and local h c of the human body in both standing and seated postures were evaluated by CFD simulations and implemented in the Fiala model to investigate the resultant influence on the predicted thermoregulatory responses by comparing the predictions with measurements of 14 human exposures. It was found that the original h c used in the Fiala model was similar to the simulated h c of the standing body, but higher than that of the seated body at most body parts. In 64% of the investigated human exposures, the root-mean-square-deviation of the skin temperature predicted by the Fiala model with the simulated h c was lower than that achieved with the original h c, indicating an improvement of the accuracy of the Fiala model. Additionally, the higher h c of the standing body resulted in a lower mean skin temperature by up to 1.5 °C when compared to the seated body in the environment of 10 °C and 2.5 m/s. This emphasises the necessity of ensuring the accuracy of the h c in the thermoregulation model in order to improve its validity for specific investigated conditions. Highlights: The impact of the body posture on convective heat transfer coefficient expands with the air speed. The predicted human skin temperature varies with body posture. Accuracy of the Fiala model is increased by using simulated convective heat transfer coefficients.